Ability of Curcuminoid from Curcuma domestica Val. in Reducing the Secretion of Reactive Oxygen Intermediates by Synovial Fluid Monocytes in Patients with Osteoarthritis - Nyoman Kertia; Ahmad Husain Asdie; Wasilah Rochmah; M. Marsetyawan (Indonesian Journal of Biotechnology, 2011)
Increasing the secretion of reactive oxygen intermediates (ROI) by monocytes in the synovial fluid is anindicator to determine the severity of joint inflammation. Previous studies have shown that curcumin inhibitthe osteoarthritis progression with its ability to inhibite the activity of the nitric oxide synthase (NOS) enzymefrom macrophages. In this prospective randomized open end blinded evaluations = PROBE study, 80 patientswith knee osteoarthritis were eligable. The subject were devided in to two group: group who received 3 x 30mg of curcuminoid from Curcuma domestica Val. extract (curcuminoid group) and group who received 3 x 25mg of diclofenac sodium (diclofenac group) as comparison. The treatment was for 4 weeks time. The secretionof ROI by sinovial fluid monocytes was calculated by scoring the amount of formazan formation after neutralred staining in nitrobleu tetrazolium reduction assay. The result of this study showed that the secretion of ROIby synovial fluid monocytes was significantly decreased in both groups (p <0.001) respectively. There wasno significant difference in decreasing of ROI secretion of synovial fluid monocytes between both treatmentgroups (p = 0.92).